Systematic review and meta‐analysis: Association of a pre‐illness Western dietary pattern with the risk of developing inflammatory bowel disease. Issue 7 (22nd July 2020) - Li, Tong; Qiu, Yun; Yang, Hong Sheng; Li, Man Ying; Zhuang, Xiao Jun; Zhang, Sheng Hong; Feng, Rui; Chen, Bai Li; He, Yao; Zeng, Zhi Rong; Chen, Min Hu
Abstract : Objective: Previous studies have presented conflicting results on Western diets and the risk of inflammatory bowel disease (IBD). This study aimed to evaluate the role of a pre‐illness Western dietary pattern in the development of IBD. Methods: The Western dietary pattern was defined as that met at least two of the following, either a high intake of refined grains, red and processed meat, animal protein, animal fats or high‐fat dairy products, or with a low consumption of fruit and vegetables. Four medical databases (PubMed, EMBASE, the Cochrane Library and the China National Knowledge Infrastructure) were searched to identify all relevant references. Risk estimate and corresponding 95% confidence interval (CI) were pooled using a random‐effects model. Results: Nine studies (seven case‐control studies and two prospective cohorts) were included, with a total of 1491 IBD cases and 53 089 controls. A Western dietary pattern was associated with a risk of all IBD (relative risk [RR] 1.92, 95% CI 1.37‐2.68) and separately with Crohn's disease (CD) (RR 1.72, 95% CI 1.01‐2.93) and ulcerative colitis (UC) (RR 2.15, 95% CI 1.38‐3.34). Subgroup analysis by region showed that a Western dietary pattern was associated with the risk of CD and UC for studies performed in Europe (RR 2.25, 95% CI 1.44‐3.50 for CD; RR 2.65, 95% CI 1.61‐4.36 for UC). The pooled RR was 2.26 (95% CI 1.42‐3.59) in the pediatric CD subgroup. Conclusion: This meta‐analysis indicates that a pre‐illness Western dietary pattern may increase the risk of developing CD and UC.